ANALYSIS OF THE EFFECTIVENESS OF USING SOCIAL MEDIA IN INCREASING BRAND AWARENESS IN MSMEs IN KENDARI CITY - kartika, Bunga Kartika; Muh. Husriadi (Noble Cendekia Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Kendari City face the challenge of low brand awareness amidst the post-pandemic digital transformation, with only 28% active on social media due to limited infrastructure and minimal digital literacy. This study aims to analyze the effectiveness of social media use in increasing brand awareness of MSMEs in Kendari City through local adoption and engagement patterns. A descriptive qualitative method with data triangulation was applied to 15 purposive informants, using semi-structured interviews and observations of Instagram/TikTok accounts. Results show that easy adoption and relative advantage drive a twofold increase in turnover and top-of-mind recall via Muna/Tolaki cultural content, although internet signal constraints moderate effectiveness.